Platelet/Lymphocyte Ratio Accuracy as Predictor of Neo-Adjuvant Chemotherapy Response in Locally Advanced Breast Cancer at Dr. Mohammad Hoesin General Hospital Palembang - Abdur Rahman; Mulawan Umar; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Platelet/lymphocyte ratio (PLR) is considered as predictor for chemotherapy response in locally advanced breast cancer undergoing neo-adjuvant chemotherapy. This study aims to evaluate the relationship between the platelet/lymphocyte ratio and neo-adjuvant chemotherapy response in patients with locally advanced breast cancer at Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study is a prognostic test of the platelet/lymphocyte ratio accuracy to predict the response of neo-adjuvant chemotherapy in patients with locally advanced breast cancer. The study included 113 subjects. Results: From 113 patients, the PLR cut off point value was 206.83 with an under curve area (AUC) of 91.8%. The results of the PLR prognostic test were sensitivity of 98%, specificity of 87%, Positive Predictive Value of 95%, Negative Predictive Value of 93%, and 95% of accuracy. There was a significant relationship between PLR and chemotherapy response in patients with locally advanced breast cancer (p = 0.000). Conclusion: There was a significant relationship between PLR on chemotherapy response. PLR can be used as a predictor of neo-adjuvant chemotherapy response with a good degree of accuracy.